Au Congrès d'Amsterdam : discours - Guesde, Jules; Bebel, August; Vaillant, Édouard (Paris : Parti Socialiste de France, 1904)
Fonds Perrone
Frans
Brochure
Keywords: Tweede Internationale (1889-1919).; socialistische partijen; Frankrijk